Biomineralization control related to population density under ocean acidification - Goffredo, Stefano (2014)
Anthropogenic CO(2) is a major driver of current environmental change in most ecosystems(1), and the related ocean acidification (OA) is threatening marine biota(2). With increasing pCO(2), calcification rates of several species decrease(3), although cases of up-regulation are observed(4). Here, we show that biological control over mineralization relates to species abundance along a natural pH gradient. As pCO(2) increased, the mineralogy of a scleractinian coral (Balanophyllia europaea) and a mollusc (Vermetus triqueter) did not change. In contrast, two calcifying algae (Padina pavonica and Acetabularia acetabulum) reduced and changed mineralization with increasing pCO(2), from aragonite to the less soluble calcium sulphates and whewellite, respectively. As pCO(2) increased, the coral and mollusc abundance was severely reduced, with both species disappearing at pH < 7.8. Conversely, the two calcifying and a non-calcifying algae (Lobophora variegata) showed less severe or no reductions with increasing pCO(2), and were all found at the lowest pH site. The mineralization response to decreasing pH suggests a link with the degree of control over the biomineralization process by the organism, as only species with lower control managed to thrive in the lowest pH.